Real Union in Leibniz’s Political Thought: The Role and Value of the Mystical Body in Civil Bodies - Manzo, Fiorenza (Religions, 2024)
This paper explores the idea, occasionally discernible in Leibniz’s writings, that civil bodies can achieve a real or substantial union through the ’mystical body’ of the Church. The starting question is: can the ‘person’ of the state attain real internal union even if it is not a natural person? This theme is examined in light of Leibniz’s interest in the ontology of complex aggregates (including civil ‘bodies’ or ‘persons’), the miracle of the Eucharist, the mystery of transubstantiation, and the unity of the Church. Since his very early Demonstrationes Catholicae, he had strived to demonstrate that the body of the Church, despite being—so to speak—‘scattered’, can be regarded as a Respublica with a strong internal degree of unity, primarily due to the communion that the faithful share through the Eucharist. This article thus analyses both early and mature texts in which Leibniz discusses the bond established among the faithful by the presence of Christ in the Eucharist, arguing that he experimented with the idea that the spiritual union possible within the Church’s ‘mystical body’ and its aggregative capacity could transform European Christian states not only politically but also substantially.